Studying the factors affecting the recognition of traffic signs in the conditions of Syrian cities - درويش عبير; شذى أسعد; أكرم رستم (Latakia University Journal -Engineering Sciences Series, 2023)
The Traffic signs are usually one of the most important factors affecting increasing traffic safety and reducing the economic burden resulting from traffic accidents. Understanding the signs is important for effective driving, responding to warnings and finding ways, and organizing the movements of road users by highlighting priorities and informing road users of traffic regulations and conditions, and the signs that Poorly understood increases the risk of accidents and may endanger road users. In this research, the level of drivers’ understanding of traffic signs was measured by conducting a field survey of a group of signs to be evidence of drivers’ awareness of these signs, and the current situation of the signs on some urban roads was evaluated by selecting urban streets in the cities of Lattakia and Tartous, Conducting a statistical analytical study of the current status of traffic signs and the criteria affecting their identification, and studying the extent to which drivers know and pay attention to traffic signs in general, which are present on the roads. The results of the study provided data for the modification of traffic sign design criteria, on the streets of the cities of Latakia and Tartous, with the need to rehabilitate the old traffic signs, to better understand the meanings of all the signs.